How do Online Comments Affect Perceived Descriptive Norms of E-Cigarette Use? The Role of Quasi-Statistical Sense, Valence Perceptions, and Exposure Dosage. Issue 1 (17th December 2018) - Liu, Jiaying; Shi, Rui
Abstract: By facilitating user participatory features such as online comments, digital media expand the means through which individuals can get access to others' behavior choices. This opens new research avenues in the pursuit of understanding how social influence operates in the virtual space. The current study examined whether anonymous others' behavior choices within the online comment board may affect viewers' descriptive norm perceptions in the real world. Results show that, given sufficient total exposure, viewers' "quasi-statistical sense" allowed them to correctly identify the numerical majority through subtle individual behavior cues embedded in the online comments, which effectively influenced their estimation of the actual e-cigarette use prevalence among the U.S. population. Perceived behavior choice dominance and valence stance dominance toward e-cigarette use on the online comment board were found to mediate the relationship. Implications for the underlying mechanism of descriptive norm perception formation and future directions are discussed.